Minimization of pollution from paddy fields activities in Kedah: Muda Agricultural Development Authority (MADA) Perspective - Yaacob, Nurul Fatini; Salleh, Nurul Azita (Universiti Utara Malaysia, 2020)
Each sector has its problems. Haze is a common problem in sectors such as the manufacturing sector, and the agricultural sector. The excessive haze will cause problems for the environment and will, in the long run, affect the existing ecosystem. Not only haze becomes a problem for each sector but sometimes air, soil and noise pollution also happen in each sector. Therefore, this study aims to minimize pollution in the paddy field. Agriculture industry benefits in economic growth. However, it contributes to the negative impact on the environment. Thus, this study focused on identifying the types, factors, and solutions to pollution in the agriculture industry based on the pollution from paddy field activity in Kedah. This study conducted qualitative research methods. The respondents are top management from the Muda Agricultural Development Authority (MADA) which located in Kedah. The result showed that activity from the paddy field has various types of pollution such as water, air, and soil. Meanwhile, the pollution caused by the open burning, the use of inorganic fertilizers, less use of the latest technology and the technology available is very limited and inadequate due to high demand. The results of this study provide a solution to the pollution caused by activities in paddy fields such as using the ‘Jerami Gulung’ Method, reduce the use of chemical fertilizers, using the incinerator, makes it a compost, turning straw into livestock and using the straw grinding machine. As implications, this study of raising farmers' awareness to reduce excessive use of chemical fertilizers, not burning straw and raising awareness among MADA and Environment Agency on smart ways to conserving and preserving the environment.